Migration and Tourism - TIMČÁK, Gejza M.; JABLONSKÁ, Jana; ONDREJOVÁ, Barbora (Journal of Environmental Management and Tourism, 2017)
Migration can be a part of tourism related processes and there are numerous types of migrants and migration processes. The paper investigates the possible connection between tourism related processes and the present wave of migration to EU. Further, it analyzes the impact of the present migration processes on natural, cultural and social environment. Then the question of impact of migration and of war on a development of new forms of tourism and tourism related services. Finally, using the results of a survey, the impact of migration on the outlook and pre-purchase considerations of potential tourism clients is analyzed.